The Impact of Coastal Tourism Activities on Water Quality at Baluran National Park - Nike Ika Nuzula; Haryo D. Armono; Daniel M. Rosyid (IPTEK The Journal for Technology and Science, 2017)
Baluran is a national park identified as biologically and nun-biologically rich area in East Java. It has physical landscapes with high tourism potential. In the past five years, tourists visit has significantly increased, where leds to water quality degradation around the coast. The aim of this research is to determine the relationship between tourists visit and water degradation phenomena in the area of study. The PCA (Principal Component Analysis) and IPL (Environmental Pollution Index) is used for analysis. Research was performed in the rainy and dry seasons. The correlation of water quality parameters in dry season is higher than in the rainy season. Water environment pollution index is 0.027 (category not polluted) in dry season and 0.48 (category not polluted) in rainy seasons.